Happiness unlimited: awakening with Brahma Kumaris - Shivani (New Delhi, 2015)
The book, 'Happiness Unlimited: Awakening With Brahmakumaris is based on the popular television show, 'Awakening with Brahma Kumaris'. This television show revealed how and why we think and behave in certain ways and brought into limelight the perceptions and strong beliefs which influence our thoughts and feelings. The show helped millions of viewers to unravel the journey of self-transformation. The book is a compilation of all the teachings and sayings imparted in this show. It is written by Sister Shivani, a famous motivational speaker and Suresh Oberoi. The writings in the book are highly inspirational and are helpful in dealing with daily problems like lack of inspiration, mental illness, fatigue and stress. The focus of the book is on the concept of 'Happiness' which is often misunderstood by us. One of the grave mistakes people often make is that they link happiness with some person, thing or a place. Making happiness dependent on other things actually pushes us away from it. We think we will be happy in the future but we seldom ask why we will be happy in the future and not now. Real happiness comes with acceptance. When we start accepting people as they are, we follow the path of happiness. We have the choice of living a life of joy, contentment and bliss; because we have the power and the will to make things happen. Happiness is a actually a decision. A decision to take complete control of our lives, a decision to take responsibility of whatever happens in our life and the decision to not play the blame game anymore. All these ethos are well reflected in this book. About the author :- Sister Shivani is an inspirational speaker and a Brahma Kumaris teacher and a member of the Brahma Kumaris World Spiritual University since the last two decades. She rose to fame with the television series "Awakening with Brahma Kumaris. She won the Women of the Decade Achievers Award by ALL Ladies League in 2014.
Keywords: Happiness